Sistem Informasi Penentuan Lokasi Pembangunan Kawasan Industri di Kabupaten Mojokerto Menggunakan Metode Multi-Creteria Evaluation Berbasis WEB-GIS - Diky Dwi Junianto; Fatwa Ramdani; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Economic growth is something that must be achieved by every government, to promote the welfare of the community of its territory. One step to accelerate economic growth is to build an industrial estate. Industrial area is the centraled of processing industry activities. Industrial activity will absorb labor and increase taxes for the region. The choice of location of industrial estate development must be determined precisely because it will affect the smoothness of industrial operation, public convenience, and environment preservation. To determine the exact location of the industrial estate is very difficult, because the coverage of a large area and must consider many aspects in its development. On this research to developed information system to determine the location of industrial estate in Kabupaten Mojokerto. The system utilizes spatial analysis of QuantumGIS applications, Landsat-8 satellite image data (acquired on of May 20, 2017), multi criteria evaluation method, AHP method and regulation of the Minister of Industry of the Republic of Indonesia number 35 / M-IND / PER / 3/2010 on guidelines technical area of industry as guideline for determining industrial estate. The result of this research is information system of location determination of location of industry based on webGIS (Website Geography Information System). Performance testing and ROC curve testing. The results of performance testing showing excellent system performance, evidenced by the test results of all HTTP requests of all successful features. While the results of ROC curve accuracy testing showed a level of accuracy of 78%, indicating accurate accuracy. The purpose of this system is to inform the land area for the suitability of the industrial estate based on the scale of conformity (very appropriate, appropriate, less inappropriate, inappropriate).